TEORI TITIK TETAP DI RUANG METRIK PARSIAL TERURUT FIXED POINT THEORY IN ORDERED PARTIAL METRIC SPACES - , AHMAD ANSAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this Thesis, we discussing about existence and uniqueness of a fixed point in ordered metric spaces and ordered partial metric spaces using a weakly contractive mapping. Further, we prove existence of a fixed point in ordered partial metric spaces using a generalized weakly contractive mapping.